Edukasi Pentingnya Sanitasi Makanan untuk Pencegahan Penyakit Diare di TPA Masjid Nurul Iman Kecamatan Kendari Barat, Kota Kendari - Karimuna, Siti Rabbani; Taoha, Aurel Amelia Putri; Sabara, Mega; Saputri, Rizda Sandiva; Safitri, Selvi; Pratiwi D, Siska Shafrianti; Muliani, Sri; Astuti, Tina Sesarya; Taufik, Aliyyah Nisrina; Sasono, Ihsan Adi (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
Diarrhea is a condition characterized by the frequency of defecation more than three times a day with watery stools, sometimes accompanied by blood or mucus. This research aims to provide adequate knowledge to children about the importance of maintaining personal hygiene and environmental sanitation to avoid health problems such as diarrhea, especially at Nurul Iman TPA on Jalan Dr. Moh. Hatta, West Kendari District, Kendari City, Southeast Sulawesi. Implementation of the activity begins with an introduction and explanation of the purpose of the activity. Next, a questionnaire was given in the form of a pre-test (initial test) to measure children's knowledge about diarrhea. After that the material is delivered, followed by a post-test (final test) for evaluation after counseling. The research results showed a p-value of 0.000 < 0.05, which indicated a significant change in the level of knowledge between before and after counseling. Thus, the alternative hypothesis is accepted and the null hypothesis is rejected, indicating that the knowledge of TPA Nurul Iman students increased significantly after counseling. Diarrhea is often caused by poor hygiene and infections from bacteria, viruses or parasites. Education regarding the importance of personal hygiene, such as washing hands with soap (CTPS), is an effective preventive measure.